2012
DOI: 10.2139/ssrn.2165889
|View full text |Cite
|
Sign up to set email alerts
|

A Radical Change in Traffic Law: Effects on Fatalities in the Czech Republic

Abstract: I evaluate the effects of a new road traffic law in the Czech Republic that became effective on July 1, 2006. The law introduced tougher punishments through the introduction of a demerit point system and a manifold increase in fines, together with an augmented authority of traffic police. I find a sharp, 33.3 percent, decrease in accident-related fatalities during the first three post-reform months. This translates into 51 to 204 saved lives with 95 percent certainty. The decline was, however, temporary; estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A larger spread in speeds may boost accidents and traffic congestion according to Lave (1985), Aarts and van Schagen (2006) and Elvik (2014). Less aggressive driving at lower speeds however contribute to lower accidents according to Aarts and van Schagen, 2006, van Benthem, 2015, Rodriguez (1990 and Montag, 2014. Lower speeds also generate less noise pollution, see Bendtsen (2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A larger spread in speeds may boost accidents and traffic congestion according to Lave (1985), Aarts and van Schagen (2006) and Elvik (2014). Less aggressive driving at lower speeds however contribute to lower accidents according to Aarts and van Schagen, 2006, van Benthem, 2015, Rodriguez (1990 and Montag, 2014. Lower speeds also generate less noise pollution, see Bendtsen (2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…2 The road accidents lead to severe injuries. 3 It is estimated that worldwide 8,56,000 road expiries occur annually. Among them, almost 74% occur in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…This may seem to be an extreme prediction. Consider, however, that Montag (2014) investigated the effects of a substantial increase in sanctions for traffic law offenses in the Czech Republic, and found that the immediate effect of such a change was a one third decline in road-traffic-accident-related fatalities. However, a quick rebound followed within the ensuing months and there was no identifiable effect beyond one year after the reform.…”
Section: Introductionmentioning
confidence: 99%